Synthesis, characterization and antibacterial activity of novel poly(silyl ether)s based on palm and soy oils - Mohammed, Issam Ahmed; Shahabuddin, Syed; Khanam, Rashmin; Saidur, Rahman (Associacao Brasileira de Polimeros, 2018)
In this research, palm oil and soy oil were used as a natural polyol to prepare novel poly(silyl ether)s. Palm oil and soy oil were first converted to monoglyceride by one step via alcoholysis process in the presence of 0.1% CaO as a catalyst. The monoglycerides were characterized by Fourier transform infrared spectrometer (FT-IR), nuclear magnetic resonance (NMR) and iodine test. The novel poly(silyl ether)s were prepared via polycondensation reaction between dimethyldichlorosilane with monoglycerides based on palm and soy oils, respectively. FT-IR, NMR and silicone-29 ( 29 Si NMR) were used to confirm and determine the presence of silicone in the synthesized polymers. Thermal behavior was studied by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Antibacterial activity of the polymers was screened against three different strains of bacteria, namely Escherichia coli E266, Staphylococcus aureus S276 and Salmonella choleeraesuis 10708.